Characteristics of Vestibular Ability Development in 6-10-Year-Old Female Gymnasts - D. Petran; G. Toma; V. Jurat (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
This paper focuses on the vestibular ability characteristics of 6-10-year-old gymnasts. Methods. Thus, exploratory research was conducted within the CSM Arad, with 25 gymnasts aged 6-10 years, divided into two groups: A (6-7 years, n=10) and B (8-10 years, n=14). The Opto Jump Next system was used for testing the march in place (running in place with eyes open and eyes closed) in 10 sec. 17 parameters were measured (number of steps, contact time, flight time, pace, cycle, jumping point, tendency, and used area). The differences in the means of group A show higher values in Jumping Point (L, R) and in group B – number steps, pace (L, R), Tendency, and Used Area. All these results highlight the characteristics of vestibular ability development in 6-10-year-old gymnasts.